PERANAN SYEIKH ABDURRAHMAN SHIDDIQ DALAM PENYEBARAN AGAMA ISLAM DI INDRAGIRI HILIR - Andres Pransiska; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is (1) to know about life of Syeikh Abdurrahman Shiddiq; (2) to know the concept of religious thought Sheikh Abdurrahman Shiddiq in the run method preaching; (3) To know the development process of the spread of Islam in Indragiri Hilir; (4) To know the roles of Sheikh Abdurahman Shiddiq in the spread of Islam in Indragiri Hilir. The benefits of this research are (1) Increase and enhance the ability of researchers in writing a scientific paper (2) Adding insight regarding Sufism researchers mainly because Sufism is one thought in Islam that developed in many corners of the archipelago. In this study using qualitative research methods. Qualitative method is a method that does not use numbers in data collection and in providing interpretation of the results. Results of this study was Sheikh Abdurrahman Siddiq was a great scholar in Indragiri, in the development of Islam in Indragiri, in the year 1327 H during the reign of Sultan Mahmud was appointed as mufti Sheikh Abdurrahman Shiddiq Indragiri kingdom. The teaching role for the community Siddiq Sheikh Abdurrahman Indragiri Hilir can be seen from the efforts it does well in areas that can improve the lives and economic tarap society and in the field of education and proselytizing, has brought big changes for the public Indragiri Riau in particular and in general.Keywords: Position, Spread of Islam